The effect of Kinship marriages on the Public Hospitals in Pakistan - Asif, Shahbaz (2024)
The study summarized the effect of cousin marriages on the public health care system in terms of genetic diseases. Direct costs were estimated as well the social and psychological impact of genetic diseases on public health care.